SISTEM M-GOVERNMENT UNTUK OPTIMALISASI MANAJEMEN DATA KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN PRINGSEWU - Miswan Gumanti; Bernadhita H.S. Utami; Rita Irviani (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
The Department of Population and Civil Registration of Pringsewu Regency is an office that handles population fields such as making e-KTP, Family Cards (KK), Child Identity Cards (KIA), and Birth Certificates. In carrying out its duties as a public servant, this service does not yet have a system that can be used online so that people whose homes are far from the office experience problems in receiving these services, not to mention the requirements for making population administration sometimes not yet known by the public. This limitation makes researchers want to create a system that can be used by the community without having to come directly to the Disdukcapil office. The existence of this system is expected to help Disdukcapil employees in providing their services without being constrained by distance and time. The population data m-government (mobile government) system can be used as a source of information for both Pringsewu residents and residents outside Pringsewu regarding the terms and conditions in making population administration by simply accessing information / services by mobile.Keywords: system, m-government, population data, Department of Population and Civil Registration